Effect of interferon-α2a on neutrophil adhesion and phagocytosis in chronic myeloid leukemia and Behçet's disease - DİRESKENELİ, RAFİ HANER (My University, 2002)
Alpha-interferon (α-IFN) is implicated in a Behçet's disease (BD)-like syndrome observed in a small number of chronic myeloid leukemia (CML) patients. The effect of α-IFN on neutrophil adhesion and phagocytosis in CML patients, BD patients and healthy volunteers was investigated to clarify the reason for this observation. Ten subjects were studied for each group by incubating neutrophils with various doses of α-IFN. Basal neutrophil adhesions for CML patients, BD patients and healthy volunteers were similar. However, BD patients had greater basal phagocytosis than CML patients, and both groups had greater basal phagocytosis than healthy volunteers. Neutrophil adhesion and phagocytosis of CML patients increased following incubation with higher doses of α-IFN, and phagocytosis approached the high levels observed with BD neutrophils. This study provides evidence that α-IFN activates neutrophils in CML patients in a dose-dependent manner, and leads to a neutrophil function profile that resembles BD.
Keywords: α-Interferon; Alpha-interferon; Behçet's disease; Chronic myeloid leukemia; Neutrophil function